In Their Own Words - Scheinberg, Ellen (Archivaria, 2000)
The author reviews three books written during the 1990s which rely on oral history to explore the lives of Japanese picture brides, refugees, and female Native elders. This article reveals how these three works succeed in using oral history to give voice to the individuals from these non-hegemonic groups that had been neglected by scholars in the past. It also explores some of the pitfalls that can arise when adoptingan oral history method that fails to recognize the role of the interviewer as well as incorporate any authorial interpretation into the work. The article calls for more transparency and greater balance when producing oral histories. RÉSUMÉ L’auteure commente trois ouvrages des années 1990 basés sur l’histoireorale et destinés à explorer la vie de Japonaises mariées par correspondance, deréfugiés et de vieilles autochtones. L’article montre comment ces trois livres ont réussià utiliser l’histoire orale pour donner la parole à des personnes faisant partie de groupes non dominants et qui ont été négligés par les chercheurs dans le passé. Il explore également quelques-uns des pièges dans lesquels on peut tomber en adoptant une méthode d’histoire orale qui ne reconnaît pas le rôle de l’interviewer et qui n’intègre pas d’interprétation solide dans le travail. Dès lors, ce texte appelle à une plus grande transparence et à un plus grand équilibre lors de la production d’histoires orales.